Práticas sanitárias e percepção de risco de produtores de bovinos de corte no Pantanal de Mato Grosso do Sul - Marques Júnior, Heitor Romero [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The cattle industry is the main economic activity developed in the Pantanal of Mato Grosso do Sul. Recognized as a world heritage and biosphere reserve, the region is a major supplier of beef calves. The measures of compulsory health requirements adopted by the producers meets the guidelines of the official programs including foot-and-mouth disease, brucellosis, tuberculosis and rabies. However, most animal health actions are voluntary and depend on the initiative and interest of producers. In order to assess the perception of risk among beef cattle producers regarding the various health practices, the managers of 31 farms were interviewed in subregions Paiaguás, Nhecolândia, Abobral, Paraguai and Porto Murtinho, totaling 387.908 ha and 204.254 cattle. To analyze the related data of risk perception and health practices were considered socioeconomic factors: schooling, number of animals and length of service. The perceived risk factors were used: veterinary care, knowledge of waterborne diseases, vaccinators training, procedure in suspected case of food-and-mouth disease, knowledge and obedience to the grace period of veterinary products and disposal of corpses. The results indicate correspondence between socioeconomic factors and the model of veterinary care, the knowledge that water can transmit diseases to animals and the training of vaccinators. There was the correlation of the socioeconomic profile and the procedure in case of food-and-mouth disease suspected animals in the herd and the disposal of corpses. Producers with less schooling, fewer animals and less time in the activity have no veterinary care or have sporadically, unaware of the risks of waterborne diseases, don't develop vaccinators training, unaware and trend not to obey grace periods of veterinary products. In this condition, are very vulnerable about pet health, occupational health and environmental

A bovinocultura é a principal atividade econômica desenvolvida no pantanal de Mato Grosso do Sul. Reconhecida como patrimônio da humanidade e reserva da biosfera, a região é importante fornecedora de bezerros de corte. As medidas de ordem sanitária compulsórias adotadas pelos produtores obedecem as diretrizes dos programas oficiais que contemplam a febre aftosa, brucelose, tuberculose e a raiva. No entanto, a maioria das ações de saúde animal são voluntárias e dependem da iniciativa e interesse dos produtores. Com o objetivo de avaliar a percepção de risco entre produtores de bovinos de corte em relação a diversas práticas sanitárias, foram entrevistados gestores de 31 fazendas nas sub-regiões Paiaguás, Nhecolândia, Abobral, Paraguai e Porto Murtinho, totalizando 387.908 ha e 204.254 bovinos. Para análise dos dados relacionados à percepção de risco e práticas sanitárias foram considerados os fatores socioeconômicos: escolaridade, número de animais e tempo na atividade. Como fatores de percepção de risco utilizou-se: assistência veterinária, conhecimento da veiculação hídrica de doenças, treinamento de vacinadores, procedimento em caso suspeito de febre aftosa, conhecimento e obediência ao período de carência de produtos veterinários e destinação de cadáveres. Os resultados apontam correspondência entre fatores socioeconômicos e o modelo de assistência veterinária, o conhecimento de que a água pode transmitir doenças aos animais e o treinamento dos vacinadores. Não houve correspondência do perfil socioeconômico e o procedimento em caso de animal suspeito de febre aftosa no rebanho e a destinação de cadáveres. Produtores com menor escolaridade, menor número de animais e menor tempo na atividade não possuem assistência veterinária ou possuem esporadicamente, desconhecem os riscos da veiculação hídrica de doenças, não realizam treinamento de vacinadores, desconhecem e tendem ...
Keywords: Bovino - Criação; Percepção do risco; Analise multivariada; Pesquisa sanitaria; Pantanal Mato-grossense (MS e MT); Statistics